Dermolipoma of the Lower Eyelid. (June 2014) - Tripathy, Devjyoti; Mittal, Ruchi
Abstract Purpose: To report a rare case of isolated dermolipoma of the lower eyelid. Design: Case report. Results: A young otherwise healthy girl presenting with a slowly progressive, painless lesion of the left lower eyelid of about 3 years' duration had undergone conservative management elsewhere for symptoms of intermittent, mild irritation associated with the mass without any significant benefit. Increase in the size of the lesion in the recent past had been noted. Mass excision with histopathology showed it to be consistent with a dermolipoma. Conclusions: An eyelid dermolipoma is distinctly uncommon in occurrence. Nonetheless, it should be considered in the differential diagnosis of benign mass lesions of the eyelid.